Effect of Mixed and Intercropping of Mustard Brassica juncea (l.) Czern & Coss with Lucerne (Madicago sativa) on Soil Fertility, Water Productivity and Yield of Mustard - Singh, Jitendra; Patel, B S; Ali, Shuakat (Annals of Arid Zone, 2016)
An experiment was conducted on mixed and intercropping of mustard and lucerne during rabi and summer seasons of 2009-2010. The results indicated significantly and highest seed yield of mustard under the treatment T5 (mustard at 30 cm + broadcasting of lucerne at the time of first irrigation). Significantly and highest value of LER (2.1), mustard equivalent yield (5,812 kg ha-1) gross (Rs. 1,43,243) and net return (Rs. 1,13,230 ha-1) and water productivity (10.8 kg ha-1 m-1) were observed in treatment T7 mustard + lucerne (mixed seeds) at 45 cm + line sowing of lucerne between two rows at the time of first irrigation followed by treatments T2 and T3. The soil OC was highest under treatment T5. The sole crop and mixed and inter cropping systems exerted their significant effect on soil available nitrogen after harvest, treatment T8 (lucerne sole at 22.5 cm and seed production after third cut) established its superiority by recording available nitrogen of 169.57 kg ha-1. While, sole crop and mixed and inter cropping systems had no significant effect on available phosphorus, available potash and available sulphur, however the highest available phosphorus, available potash and available sulphur were recorded in the treatment T8. Key word: Intercropping, mixed cropping, mustard, lucerne, mustard equivalent yield, land equivalent ratio, water productivity